A flap course for orthopaedic surgeons in low-income countries: addressing a global health-care disparity - Kushal R Patel, MD; Joseph N Carey, MD; Amber M Caldwell, BA; Rick R Coughlin, MD MSc; Scott L Hansen, MD (Elsevier, 2014)
Background: The burden of complex orthopaedic trauma in low-income countries is compounded by insufficient plastic surgeons to assist in management of soft tissue injuries. To address this global health-care disparity, we created a soft tissue management course to train orthopaedic surgeons from low-income countries in flap reconstruction. Methods: The Institute for Global Orthopedics & Traumatology hosts a 3-day course to teach orthopaedic surgeons from low-income and middle-income countries flaps using cadaver dissection and didactic lectures. Precourse and postcourse assessments were used to evaluate the course's effect. Findings: In 4 years, 156 surgeons have attended the course from more than 25 different countries. Of 48 participants from the 2010 course, 90% indicated that soft tissue management training would be useful for upper extremity trauma cases and 96% for lower extremity trauma cases. A 1-year postcourse use survey was sent to all the surgeons attending the 2012 course, with 32 of 44 surgeons completing the survey. The respondents collectively undertook 594 flaps with 554 reported as successful (93•3%). Of the successful flaps, 116 flaps were believed to have prevented a subsequent amputation. 31 (97%) of 32 surgeons disseminated information to either colleagues or residents, and through dissemination of information a further 28 surgeons are now undertaking flaps. Interpretation: The skills and knowledge gained at this course by orthopaedic surgeons from low-income countries were recorded to be quickly and extensively used in their countries by our 1-year postcourse survey. This course represents a unique collaboration with physicians in low-income countries that might have the ability to provide a sustainable effect in addressing global health care disparities. Funding: None.